A century of change: rock art deterioration in the Natal Drakensberg, South Africa - Ward, V. (Southern African Humanities, 2021)
In a previous project Ward & Maggs (1994) compared Hutchinsons’ 1870s copies with the rock art as it is at present at Main Caves, Giants Castle Game Reserve, KwaZulu-Natal. In this current paper a comparison is made between the condition of rock art today with comments and copies made in 1893 by Louis E. Tylor at Giants Castle. Louis Tylor, a mining engineer and nephew of Edward Burnett Tylor of the Pitt Rivers Museum, University of Oxford, England, spent six months towards the end of 1893 recording hunter-gatherer paintings while visiting KwaZulu-Natal. He copied 85 groups, totalling 363 images at 19 sites. An additional comparison using photographs taken in 1967 by Patrick Carter and Patricia Vinnicombe is also made. The findings of the current study confirm those of the earlier project (Ward & Maggs 1994), that the nineteenth century paintings are deteriorating at a faster rate than earlier paintings. To cite this article: Ward, V. 1997. A century of change: rock art deterioration in the Natal Drakensberg, South Africa. Natal Museum Journal of Humanities 9: 75-97.